Tax evasion and voting: an experimental analysis - Feld, Lars P.; Tyran, Jean-Robert (2002)
The puzzle of tax compliance is why people pay taxes instead of evading them: Given the low expected fines, rational taxpayers should underreport taxable income. However, most taxpayers truthfully declare their income to the tax authorities, a behaviour that is usually explained by tax morale. In this paper, we study in an experimental setting which factors shape tax morale. The main result is that the higher legitimacy of an endogenous fine as compared to an exogenously determined find leads to higher tax compliance. This result is robust to competing explanations like commitment and reciprocity. - Reproduced.
Keywords: Taxation